Mycoparasitic transcription factor 1 (BcMTF1) participates in the Botrytis cinerea response against Trichoderma atroviride - Consuelo Olivares-Yañez; Nicolas Arias-Inostroza; Ruben Polanco; Paulo Canessa (iScience)
Summary: Botrytis cinerea is a phytopathogenic fungus. Traditional control using fungicides has faced challenges, prompting the exploration of sustainable alternatives such as biocontrol. Trichoderma atroviride, a promising biocontroller, is well-known for its mycoparasitism. However, the molecular processes involved in this fungal-fungal interaction, particularly regarding the defense mechanisms of the pathogen, have yet to be deeply studied. Here, we investigated the transcriptional defense responses of B. cinerea to T. atroviride. We focused on four B. cinerea transcription factors (TFs) differentially expressed during interaction with the biocontroller. Mutants lacking these TFs exhibit increased sensitivity to T. atroviride, with the Bcin07g06800 (BcMTF1) loss-of-function mutant being most susceptible. Genes predicted to be regulated by mycoparasitic transcription factor 1 were differentially expressed during this interaction. BcMTF1 influences B. cinerea’s resistance to mycoparasitism by regulating the expression of genes potentially involved in fungal defense against Trichoderma. The findings provide insights into the transcriptional processes underlying fungal-fungal interactions.